THE INFLUENCE OF VOCAL PERFORMANCE ON THE MATURITY AND GENERAL DEVELOPMENT OF STUDENTS - Абдусоматова Гулшодабегим Камолиддин кызы (Web of Journals Publishing, 2025)
This article discusses the impact of voice performance on students' maturation and overall development. The importance of vocal performance in music lessons at school and its role in developing students' aesthetic taste, creative abilities, and social skills are emphasized. In addition to helping students learn music and vocal art, vocal performance shapes their emotional world, improves their self-expression skills, and helps reduce stress. The article also examines the factors that affect students' individual and collective development through methods related to vocal exercises, voice training and music genres. Thus, it is revealed that vocal performance is an important tool that helps students achieve success in all areas, not only in the development of musical skills.
Keywords: Vocal performance, general development, music education, self-expression, aesthetic taste, social skills, emotional development, voice control, creative abilities, music education, stress reduction, choral performance.